Powerful subjects of tax law enforcement - I. Dementyev (Правоприменение)
УДК 342.6The subject. Competence of government bodies and their officials in the sphere of application of the tax law is considered in the article.The purpose of research is to determine the ratio of tax enforcement and application of the tax law, as well as the relationship between the concepts “party of tax enforcement” and “participant of tax legal relations”.Main results and scope of their application. The circle of participants of tax legal relations is broader than the circle of parties of tax law enforcement. The participants of tax legal relations are simultaneously the subjects of tax law, because they realize their tax status when enter into the tax relationships. The tax and customs authorities are the undoubted parties of the tax law enforcement.Although the financial authorities at all levels of government are not mentioned by article 9 of the Tax Code of the Russian Federation as participants of tax relations, they are parties of tax enforcement, because they make the agreement for deferment or installment payment of regional and local taxes.Scope of application. Clarification of participants of tax legal relations and determination of their mutual responsibility is essential to effective law enforcement.Conclusion. It was concluded that the scope tax law enforcement is tax proceedings, not administrative proceedings, civil (arbitration) proceedings or enforcement proceedings.The application of the tax law is carried out not only in the form of tax relations, but also in relations of other branches of law.